Ta‘līm al-Naḥw al-‘Arabī li-Ghayr al-Nāṭiqīna bi-al-‘Arabīyah ‘alá Ḍaw’ Naẓarīyat Chomsky - Ibtihal Muhammad al-Bar (Al-Ma‘rifah, 2018)
This research aims to study the concept of transformational-generative grammar by Noam Chomsky as well as the foundation of this theory and its actional principles in terms of language acquisition, and try to use the theoretical data in teaching Arabic grammar to non-native Arabic speakers. This can be done by using the analytical descriptive approach. This research is considered important because it deals with a modern linguistic theory which has a scientific value in the modern language lesson and employs it in the field of teaching Arabic grammar. The study has benefited from data of the transformational-generative grammar in the case of coping with teaching the rules of Arabic grammar to answer fundamental questions, which are: what are the foundations of transformational-generative grammar theory? What are the rules of transformational in Arabic grammar? What are the benefits of the transformational-generative grammar theory non-native Arabic speakers? The research concluded that the conscious practice of language takes place from a constructional point of view within the meaning and not just to the practical. Second language learner must be familiar with the vocal, and grammatical system in order to be able to practice the language with its rules. Finally, the aim is not to limit the linguistic attitudes in the educational process; as the generative grammar believes that a person has a tremendous ability to produce unlimited linguistic patterns of limited linguistic elements.